How mediation works : theory, research, and practice - Goldberg, Stephen B.; Brett, Jeanne M.; Blohorn-Brenneur, Beatrice; Rogers, Nancy H. (Emerald Publishing Limited, 2017)
From the leading authors in mediation and dispute resolution comes this new psychology-based work on the nuts and bolts of mediation. Using the behavioral theories of interests, rights, and power, Goldberg, Brett, and Brenneur explain what mediators do, what makes for a successful mediator, and how best to structure a mediation-essentially the role of the mediator and the disputing parties at each step of the process. Also included is an essential chapter on the relationship between mediation and the law by Nancy Rogers, one of the foremost U.S. authorities on the topic.- Resumé vydavatel
Keywords: management konfliktů; mediace; conflict management; mediation; sborníky; elektronické knihy; papers of several authors; electronic books